Pengaruh Tipe Kepribadian Big Five dan Dukungan Sosial Keluarga terhadap Work-Life Balance pada Ibu Tunggal yang Bekerja - Wira Swesty, Firizqiana; Sahrah, Alimatus; Fitriana, Nina (Program Studi Tasawuf dan Psikoterapi, 2024)
This research aims to determine the influence of the Big Five Personality Types and Family Social Support on Work-Life Balance in Single Working Mothers. The big five personality type scale, family social support and work-life balance were used to obtain data from 100 working single mothers aged 20-65 years with different work backgrounds and divorce status. Purposive sampling technique was used as a sampling method and then the research results were processed using linear regression analysis. The research results show that the big five personality type variables and family social support have varying influences on work-life balance in working single mothers. The extraversion, agreeableness and conscientiousness personality types were found to have no influence on work-life balance in working single mothers, while the emotional stability and intellect personality types and family social support had a positive influence on work-life balance in working single mothers. The contribution of the emotional stability personality type to work-life balance is 22.5%, the intellect personality type to work-life balance is 10.8% and family social support to work-life balance is 26%. Multiple regression analysis is also carried out as an additional test and has a significance value that is not different from simple regression analysis. It is hoped that the results of these findings can be a reference for personnel staff in determining policies for single mother employees as well as understanding the important personality types for single mothers who work in achieving work-life balance so that productivity and mental well-being are well maintained.